Method for regulating components of palladium-antimony-platinum catalyst and application thereof
Patent Information
- Application Number
- CN202611357091.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-23
AI Technical Summary
[0011]为克服现有技术中直接醇类燃料电池阳极催化剂存在的贵金属利用率低、催化活性不足、抗中毒能力差及长期运行稳定性欠佳等突出问题,本发明提供了一种组分比例精确可调的钯锑铂(Pd-Sb-Pt)三元合金纳米材料及其制备方法与应用
(1)本发明提供了一种一锅法合成Pd-Sb-Pt三元合金纳米材料的制备方法。该方法在温和的液相反应条件下进行,无需高温真空封管或复杂的高温高压设备,具有操作简便、反应周期短、能耗低的特点,具备良好的规模化制备前景。
Smart Images

Figure CN122968320A_ABST
Abstract
Description
Technical Field
[0001] This invention provides a palladium-antimony-platinum ternary alloy nanomaterial catalyst, and relates to the method of component regulation of the material and its application in the field of anode catalysis of direct alcohol fuel cells, belonging to the interdisciplinary field of nanofunctional materials and electrochemical catalysis technology. Background Technology
[0002] With the increasing urgency of global energy structure transformation and environmental pollution control, the development of clean and sustainable energy conversion technologies has become a core direction for promoting green social development. Direct alcohol fuel cells, due to their significant advantages such as wide availability of fuel sources, high theoretical energy density, safe and convenient storage and transportation, and environmental friendliness, have shown broad application prospects in portable power sources, mobile transportation power, and distributed power generation. However, the commercialization of direct alcohol fuel cells has long been constrained by the slow reaction kinetics of its core anode reaction—the oxidation of small-molecule alcohols. Specifically, this reaction involves multiple proton and electron transfer processes, has a complex reaction pathway, and easily generates strongly adsorbable carbonyl intermediates such as carbon monoxide. The strong chemisorption of these intermediates on the catalyst surface irreversibly occupies active sites, leading to catalyst surface poisoning and deactivation, and consequently causing a sharp decline in catalytic activity and long-term operational stability, becoming a key bottleneck restricting the improvement of fuel cell performance.
[0003] Currently, platinum (Pt)-based and palladium (Pd)-based noble metal catalysts remain the most widely used anodic catalysts for alcohol oxidation reactions in alkaline media due to their excellent CH bond breaking ability and alcohol molecule adsorption activation performance. However, the large-scale application of pure Pt or pure Pd catalysts is limited not only by resource scarcity and high cost, but more importantly, their inherent electronic structure characteristics result in excessively strong adsorption energies for carbon monoxide intermediates. This leads to an irreconcilable contradiction between the intrinsic activity and anti-poisoning ability of the catalyst, failing to meet the commercial application requirements for efficient and long-life catalysts.
[0004] To overcome the aforementioned bottlenecks, multi-metal alloying strategies are widely recognized as one of the most effective ways to improve the intrinsic activity and stability of catalysts. The main technical approaches include: (1) reducing the catalyst size to the nanoscale to increase the electrochemical active area; (2) regulating the catalyst morphology to expose more highly active crystal faces; and (3) introducing other metal elements to form alloys and regulating the electronic structure of active sites through electronic and geometric effects. In binary alloy systems, the synergistic effect between different metals has shown the potential to improve catalytic performance. For example, introducing oxygen-loving components can promote the adsorption of hydroxyl species at lower potentials, thereby accelerating the oxidative removal of intermediates through a bifunctional mechanism. However, binary alloy systems have limitations in the flexibility of electronic structure regulation, making it difficult to simultaneously optimize multiple key reaction steps such as alcohol molecule activation, intermediate conversion, and surface regeneration. In contrast, ternary alloys, by introducing a third element, provide more freedom for finely regulating the geometric structure and electronic state of the catalyst, and are expected to overcome the inherent limitations of binary systems in catalytic performance, achieving synergistic optimization of multi-step reaction pathways.
[0005] In the screening of the third component, main group p-block elements have attracted much attention due to their unique electronic configurations. Taking antimony (Sb) as an example, its unsaturated p orbitals can undergo strong orbital hybridization with the d orbitals of Pt or Pd, thereby more effectively reshaping the local electronic structure of noble metals, regulating the d-band center position, and optimizing the adsorption free energy of reactants and intermediates on the catalyst surface. Therefore, constructing a Pd-Sb-Pt ternary system is expected to combine the excellent catalytic activity of Pt / Pd with the electronic regulation and oxyphilic properties of Sb, providing a promising technical route for achieving efficient and stable electrocatalysis of alcohol oxidation.
[0006] Although the Pd-Sb-Pt ternary system shows significant advantages at the theoretical level, it still faces a series of technical challenges that need to be addressed in practical preparation and application.
[0007] First, achieving precise control of component ratios and uniformity of nanostructures is difficult. Due to the significant differences in the standard reduction potentials and atomic radii of Pd, Pt, and Sb, achieving controllable co-reduction and uniform alloying of these three at the nanoscale is extremely challenging. In existing synthesis methods, changes in the amount of any precursor often cause significant alterations in the morphology, size, crystal phase, and surface defect structure of the nanoparticles. This high coupling between composition and structure makes it impossible to independently distinguish the true contribution of each element to catalytic performance, severely restricting the rational design and targeted screening of highly efficient catalysts.
[0008] Secondly, existing synthesis methods suffer from drawbacks such as demanding conditions, high energy consumption, and poor morphology controllability. Currently reported Pd-Sb-Pt ternary alloy preparations mostly rely on high-temperature vacuum tube-sealing solid-state methods or high-temperature hot-injection methods. These methods not only require expensive high-vacuum equipment and prolonged high-temperature processing, resulting in huge energy consumption and long preparation cycles, but also typically produce micron-sized irregular blocky aggregates or particles with a wide particle size distribution, exhibiting extremely poor morphological uniformity. More importantly, the materials prepared by these methods have low electrochemical active areas and require additional physical confinement methods (such as loading onto a specific carbon substrate) to prevent particle agglomeration. This further limits the full realization of their catalytic performance, making it difficult to meet the practical needs of large-scale preparation and application.
[0009] Third, existing methods struggle to achieve controllable adjustment of product composition and structure. Due to the high temperature and energy consumption of current synthesis methods, the reaction process is poorly controllable. It is impossible to achieve continuous and precise control of product component ratios through simple adjustments to process parameters, nor is it easy to systematically optimize the alloy composition while maintaining a relatively consistent nanostructure. This prevents researchers from flexibly adjusting material formulations according to actual catalytic needs, severely limiting the application expansion and performance improvement of such materials in the field of alcohol oxidation electrocatalysis.
[0010] Therefore, developing a method for preparing Pd-Sb-Pt ternary alloy catalytic materials that can achieve precise tunability of composition and maintain high consistency of nanostructure under mild conditions and through simple processes is the key to breaking through the current performance bottleneck of alcohol oxidation electrocatalysts and is also a core technical problem that urgently needs to be solved in this field. Summary of the Invention
[0011] To overcome the prominent problems of low precious metal utilization, insufficient catalytic activity, poor resistance to poisoning, and unsatisfactory long-term operational stability in existing direct alcohol fuel cell anode catalysts, this invention provides a palladium-antimony-platinum (Pd-Sb-Pt) ternary alloy nanomaterial with precisely tunable component ratios, its preparation method, and its applications. This invention achieves continuous control of the ternary alloy component ratios while maintaining a high degree of nanostructure consistency through a mild one-pot synthesis strategy. The resulting catalyst exhibits excellent catalytic activity and operational stability for the electrocatalytic oxidation of various small-molecule alcohols such as methanol, ethylene glycol, and glycerol, significantly improving the utilization efficiency of precious metals. This provides a practical technical solution for the design and development of high-performance direct alcohol fuel cell anode catalysts.
[0012] On the one hand, the present invention provides a method for controlling the composition of a palladium-antimony-platinum catalyst, comprising the following steps: A certain amount of palladium metal precursor, platinum metal precursor, platinum metal precursor, structure directing agent, reducing agent and solvent are sealed and mixed evenly, and then heated to react for a period of time. After the reaction is completed, the mixture is cooled to room temperature to obtain a nanomaterial solution. After the reaction is completed, the palladium-antimony-platinum nanomaterial is washed, dried and then loaded with carbon black to obtain a palladium-antimony-platinum catalyst.
[0013] The palladium metal precursor is palladium acetylacetonate; the platinum metal precursor is platinum acetylacetonate; the platinum metal precursor is triphenylantimony; the structure directing agent is molybdenum hexacarbonyl; the reducing agent is L-ascorbic acid; and the solvent is oleylamine. The ratio of acetylacetone palladium, triphenylantimony, acetylacetone platinum, hexacarbonyl molybdenum, L-ascorbic acid to oleylamine is 1 mg : 1 mg : 1~5 mg : 0.5 mg : 6 mg : 1 mL.
[0014] The heating reaction temperature is 100~140 ℃; the reaction time is 80~150 minutes.
[0015] Furthermore, by adjusting the amount of platinum acetylacetonate added, palladium-antimony-platinum ternary alloy nanomaterials with different component ratios can be prepared, wherein the component ratios include, but are not limited to: Pd 50 Sb 31 Pt 19 Pd 40 Sb 31 Pt 29 Pd 27 Sb 23 Pt 50 Pd 25 Sb 21 Pt 54 Pd 23 Sb 19 Pt 58 .
[0016] The washing process is carried out in two steps. First, the washing is performed with a chloroform / ethanol solution, wherein the volume ratio of chloroform to ethanol is 1:(5~7); then, the washing is performed with an ammonium thiocyanate / acetone solution, wherein the volume ratio of ammonium thiocyanate to acetone is (30~70) mg:1 mL.
[0017] The step of loading the palladium-antimony-platinum nanomaterials with carbon black is as follows: the mass ratio of dried palladium-antimony-platinum nanomaterials to carbon black is 1:3, and the carbon black is Super P type carbon black.
[0018] On the other hand, the present invention provides the application of the palladium-antimony-platinum catalyst prepared by the above method in the electrocatalytic oxidation of alcohols, specifically including the following steps: (1) The palladium-antimony-platinum catalyst was dispersed in ethanol, and then deionized water and naphthol were added. The mixture was then ultrasonically mixed to obtain a palladium-antimony-platinum catalyst dispersion. (2) The palladium-antimony-platinum catalyst dispersion from step (1) is uniformly coated onto the surface of a glassy carbon electrode and dried to obtain the palladium-antimony-platinum working electrode. (3) Test the electrocatalytic oxidation performance of different alcohols in a three-electrode system using the working electrode of step (2), with the Hg / HgO electrode as the reference electrode and the platinum mesh electrode as the counter electrode. Use 1 M KOH solution containing 1 M methanol, 1 M ethylene glycol or 1 M glycerol as the electrolyte. Test the electrocatalytic oxidation performance of alcohols in a three-electrode system on an electrochemical workstation.
[0019] In step (1), the ratio of the palladium-antimony-platinum catalyst, ethanol, deionized water and naphthol is 1 mg: 500 μL: 500 μL: (15~20) μL, wherein the mass percentage concentration of naphthol is 10%.
[0020] Compared with the prior art, the present invention has the following advantages: (1) This invention provides a one-pot method for synthesizing Pd-Sb-Pt ternary alloy nanomaterials. This method is carried out under mild liquid-phase reaction conditions, without the need for high-temperature vacuum sealing tubes or complex high-temperature and high-pressure equipment. It has the characteristics of simple operation, short reaction cycle and low energy consumption, and has good prospects for large-scale preparation.
[0021] (2) By simply adjusting the amount of platinum precursor, the present invention can achieve continuous and precise control of the proportion of Pd / Pt / Sb components in the ternary alloy. In this process, the particle size and branched morphology of the alloy nanomaterial remain highly consistent, which solves the technical problem of uncontrollable structural changes accompanied by changes in composition in the prior art.
[0022] (3) The Pd-Sb-Pt ternary alloy nanomaterials prepared by this invention have a uniform component distribution and a regular nanobranch structure, providing abundant electrochemical active sites and effectively improving the utilization rate of noble metal atoms.
[0023] (4) The Pd-Sb-Pt ternary alloy catalyst prepared in this invention exhibits excellent catalytic activity for the electrocatalytic oxidation of methanol, ethylene glycol, and glycerol in alkaline media. Its mass activity and specific activity are significantly better than those of binary Pd-Sb alloys and commercial Pd / C catalysts. Among them, the optimal doping ratio of Pd... 27 Sb 23 Pt 50 The nanocatalyst exhibits a high mass activity of 4.21 A / mg for the oxidation of methanol, ethylene glycol, and glycerol in alkaline media. Pd+Pt 7.59 A / mg Pd+Ptand 3.95 A / mg Pd+Pt The specific activities for the oxidation of methanol, ethylene glycol, and glycerol are as high as 30.39 mA / cm. 2 54.57 mA / cm 2 and 28.52 mA / cm 2 This demonstrates the universal catalytic advantage of this ternary alloy system for alcohol substrates with different carbon chain lengths.
[0024] (5) The catalyst of the present invention has excellent resistance to poisoning and long-term operational stability. Its catalytic performance decays slowly after long-term continuous operation, which is significantly better than binary alloys and commercial catalysts, thus improving the requirement for long-life service of anode catalysts in direct alcohol fuel cells.
[0025] (6) The nanomaterials provided by this invention can be used to construct catalysts through simple ligand removal and carbon loading steps. The operation process is simple and has good potential for industrial application. Attached Figure Description
[0026] Figure 1 Pd prepared in Example 1 of this invention 50 Sb 31 Pt 19 Characterization results of ternary alloy nanomaterials; (a) is a transmission electron microscope image, (b) is an X-ray diffraction pattern, (c) is a high-angle annular dark-field scanning transmission pattern, (d) is an X-ray energy spectrum elemental distribution pattern, (e) is an X-ray energy spectrum line scan pattern, and (f) is an elemental composition analysis diagram. Figure 2 Pd prepared in Example 2 of this invention 40 Sb 31 Pt 29 Characterization results of ternary alloy nanomaterials; where (a) is a transmission electron microscope image, (b) is an X-ray diffraction pattern, and (c) is an elemental composition analysis diagram; Figure 3 Pd prepared in Example 3 of this invention 27 Sb 23 Pt 50 Characterization results of ternary alloy nanomaterials; (a) is a transmission electron microscope image, (b) is an X-ray diffraction pattern, (c) is a high-angle annular dark-field scanning transmission pattern, (d) is an X-ray energy spectrum elemental distribution pattern, (e) is an X-ray energy spectrum line scan pattern, and (f) is an elemental composition analysis diagram. Figure 4 Pd prepared in Example 4 of this invention 25 Sb 21 Pt 54Characterization results of ternary alloy nanomaterials; where (a) is a transmission electron microscope image, (b) is an X-ray diffraction pattern, and (c) is an elemental composition analysis diagram; Figure 5 Pd prepared in Example 5 of this invention 23 Sb 19 Pt 58 Characterization results of ternary alloy nanomaterials; (a) is a transmission electron microscope image, (b) is an X-ray diffraction pattern, (c) is a high-angle annular dark-field scanning transmission pattern, (d) is an X-ray energy spectrum elemental distribution pattern, (e) is an X-ray energy spectrum line scan pattern, and (f) is an elemental composition analysis diagram. Figure 6 Pd prepared for Comparative Example 1 of this invention 69 Sb 31 Characterization results of binary alloy nanomaterials; where (a) is a transmission electron microscope image, (b) is an X-ray diffraction pattern, and (c) is an elemental composition analysis diagram; Figure 7 The Pd-Sb-Pt ternary alloy catalysts with different component ratios in Example 1 and Comparative Example 1 binary Pd catalysts are examples of applications of this invention. 69 Sb 31 Comparison of the electrocatalytic methanol oxidation performance of the alloy catalyst and the commercial Pd / C catalyst in Comparative Example 2 in a mixture of 1 M KOH and 1 M methanol; where (a) is the cyclic voltammetric curve of mass activity, (b) is the cyclic voltammetric curve of specific activity, (c) is the Tafel slope, and (d) is the time-activity curve measured by chronoamperometry. Figure 8 The Pd-Sb-Pt ternary alloy catalysts with different component ratios in Example 2 and Comparative Example 1 binary Pd catalysts are examples of applications of this invention. 69 Sb 31 Comparison of the electrocatalytic ethylene glycol oxidation performance of the alloy catalyst and the commercial Pd / C catalyst in Comparative Example 2 in a 1 M KOH + 1 M ethylene glycol mixture; where (a) is the cyclic voltammetric curve of mass activity, (b) is the cyclic voltammetric curve of specific activity, (c) is the Tafel slope, and (d) is the time-activity curve measured by chronoamperometry. Figure 9 The Pd-Sb-Pt ternary alloy catalysts with different component ratios in Example 3 and Comparative Example 1 binary Pd catalysts are used in this invention. 69 Sb 31 Comparison of the electrocatalytic oxidation performance of alloy catalyst and comparative example 2 commercial Pd / C catalyst in 1 M KOH + 1 M glycerol mixture; where (a) is the cyclic voltammetric curve of mass activity, (b) is the cyclic voltammetric curve of specific activity, (c) is the Tafel slope, and (d) is the time-activity curve measured by chronoamperometry. Detailed Implementation
[0027] This invention provides a method for component control of a palladium-antimony-platinum catalyst and its application in electrocatalytic alcohol oxidation. Those skilled in the art can refer to the content of this document and appropriately modify the process parameters to achieve the desired result. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and fall within the scope of this invention. The method and application of this invention have been described through preferred embodiments. Those skilled in the art can clearly modify or appropriately change and combine the method and application described herein without departing from the content and scope of this invention to realize and apply the technology of this invention.
[0028] To address the technical bottlenecks of existing Pd-Sb-Pt ternary alloy synthesis methods, such as stringent conditions, high energy consumption, long cycles, difficulty in morphological control, and small specific surface area, this invention proposes a one-pot synthesis strategy. By designing palladium-antimony-platinum ternary alloy nanomaterials, nanoparticles with tunable composition and uniform morphology are prepared. The resulting nanomaterials possess high specific surface area and excellent mass transfer efficiency. Combined with the strong electronic synergistic effect among Pd, Pt, and Sb elements, the local electronic environment and coordination structure of the catalyst are effectively optimized, significantly reducing the reaction energy barrier of the electrocatalytic alcohol oxidation reaction and greatly improving the catalyst's activity and long-term operational stability. This invention provides a new technical route for the development of high-performance anode catalysts for direct alcohol fuel cells, with promising application prospects and industrialization potential.
[0029] The present invention will be described below with reference to specific embodiments and application examples. These embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the invention. Furthermore, after reading the specific content of this invention, those skilled in the art can gain a clearer understanding of the invention and make innovations to better apply it to the preparation of palladium-antimony-platinum alloy nanomaterial catalysts and its application in direct alcohol fuel cells.
[0030] Specifically, this invention provides a method for controlling the composition of a palladium-antimony-platinum catalyst, comprising the following steps: A) A homogeneous solution is prepared by mixing palladium precursor, platinum precursor, antimony precursor, molybdenum hexacarbonyl, L-ascorbic acid and oleylamine under ultrasonic conditions, followed by heating to obtain a nanomaterial solution. B) The nanomaterial solution is washed, dried, and then loaded with carbon black to obtain the palladium-antimony-platinum catalyst.
[0031] Wherein, the palladium precursor is palladium acetylacetonate; the platinum precursor is platinum acetylacetonate; and the antimony precursor is triphenylantimony.
[0032] According to the present invention, the mass ratio of palladium acetylacetonate, platinum acetylacetonate, and triphenylantimony is 1:(1.0~5.0):1. Specifically, it can be 1:1:1, 1:2:1, 1:3:1, 1:4:1, 1:5:1, or any of the above values as the upper or lower limit. When the amount of platinum acetylacetonate is adjusted within the above range, the Pt content in the obtained ternary alloy increases accordingly, and the Pd and / or Sb content decreases accordingly, but the alloy morphology remains stable and uniformly distributed, effectively solving the problem of structural disorder accompanying component adjustment in the prior art. Furthermore, when the mass ratio of platinum acetylacetonate to palladium acetylacetonate is 3:1, the obtained ternary alloy achieves the optimal balance between catalytic activity and stability.
[0033] In some specific embodiments, in step A), the reaction temperature is 100~140℃; specifically, it can be 100℃, 110℃, 120℃, 130℃, or 140℃; the reaction time is 80~150 min; specifically, it can be 80 min, 90 min, 100 min, 110 min, 120 min, 130 min, 140 min, or 150 min; preferably, the above values are the upper or lower limits. Within this temperature and time range, the metal precursors can react fully and achieve uniform alloying, while the carbon monoxide gas generated by the decomposition of molybdenum hexacarbonyl can effectively regulate the anisotropic growth of nanocrystals, forming a branched structure that is conducive to the catalytic reaction.
[0034] In this invention, the preferred mass ratio of the palladium precursor to molybdenum hexacarbonyl is 1:0.5. During the reaction, the molybdenum hexacarbonyl acts as a structure-directing agent; the carbon monoxide produced by its decomposition can selectively adsorb onto specific crystal faces, regulating anisotropic crystal growth and thereby inducing the formation of branched nanostructures, increasing the exposure ratio of catalytic active sites.
[0035] In this invention, the preferred mass ratio of the palladium precursor to L-ascorbic acid is 1:6. L-ascorbic acid, as a mild reducing agent, can gradually reduce the three metal precursors to zero-valent metal atoms, providing a suitable reduction kinetic environment for subsequent alloy nucleation and growth.
[0036] The reaction solution was further washed and dried, and then loaded with carbon black to obtain the palladium-antimony-platinum catalyst.
[0037] In some specific embodiments, step B) involves centrifuging and washing the reaction solution cooled to room temperature. The centrifugation and washing are performed as follows: the reaction mixture cooled to room temperature is centrifuged, and the supernatant is discarded; chloroform and ethanol are added to the resulting precipitate, and the mixture is dispersed evenly under ultrasonic conditions and centrifuged again; the above centrifugation-washing operation is repeated multiple times; subsequently, the obtained nanomaterials are finally washed with a mixed solution of acetone and ammonium thiocyanate; after washing, the bottom precipitate is collected and dried at room temperature to obtain the palladium-antimony-platinum ternary alloy nanomaterials.
[0038] In this invention, the volume ratio of chloroform to ethanol is preferably 1:(5~7), specifically 1:5.5, 1:6, 1:6.5, or any of the above values as the upper or lower limit. During centrifugation and washing, chloroform is used to dissolve residual organic ligands and unreacted precursors in the system, while ethanol is used to adjust the polarity of the dispersion and induce the aggregation and sedimentation of nanoparticles; the synergistic effect of the two can efficiently remove impurities and significantly improve product purity without damaging the product composition and structure.
[0039] In this invention, the preferred ratio of acetone to ammonium thiocyanate is 1 mL : (30~70) mg, specifically 1 mL : 40 mg, 1 mL : 50 mg, or 1 mL : 60 mg, or any of the above values as the upper or lower limit. During the washing process using a mixed solution of ammonium thiocyanate and acetone, the thiocyanate ions in ammonium thiocyanate can compete for coordination with the oleylamine ligands remaining on the surface of the nanomaterials, effectively replacing and removing the surface-adsorbed organic molecules. Acetone promotes the dissolution and desorption of the ligand-ammonium thiocyanate complex. The synergistic effect of the two can significantly improve the surface cleanliness of the final product, expose more metal active sites, and thus improve catalytic performance.
[0040] This invention achieves precise control over the nucleation and growth process of ternary alloys by adjusting the feeding ratio of palladium, platinum, and antimony precursors, synergistically utilizing the regulatory effects of molybdenum hexacarbonyl and L-ascorbic acid, and the dispersing and protective functions of oleylamine. This results in palladium-antimony-platinum ternary alloy nanomaterials with uniform composition, uniform particle size, and excellent catalytic activity. This invention provides a palladium-antimony-platinum ternary alloy nanomaterial prepared by any of the preparation methods described in the above-mentioned technical solutions. The preparation methods described above have been clearly described and will not be repeated here.
[0041] This invention provides an electrocatalyst for alcohol oxidation, characterized in that the catalyst contains a palladium-antimony-platinum ternary alloy nanomaterial, wherein the palladium-antimony-platinum ternary alloy nanomaterial is in the form of independently existing nanoparticles or in the form of nanoparticles supported on the surface of a support; and the palladium-antimony-platinum ternary alloy nanomaterial is prepared by any of the methods described above.
[0042] In this invention, the carrier is preferably a carbon carrier, and more preferably carbon black. The mass ratio of the palladium-antimony-platinum nanomaterial to the carrier is preferably 1:3.
[0043] The application of the palladium-antimony-platinum catalyst prepared in this invention in the electrocatalytic alcohol oxidation catalyst includes the following specific steps: (1) The palladium-antimony-platinum catalyst was dispersed in ethanol, and then deionized water and naphthol were added. The mixture was then ultrasonically mixed to obtain a palladium-antimony-platinum catalyst dispersion. (2) The palladium-antimony-platinum catalyst dispersion is coated on the surface of a glassy carbon electrode and allowed to stand and dry to obtain a working electrode loaded with an electrocatalytic alcohol oxidation catalyst. (3) The working electrode of step (2) was tested in a three-electrode system to test the electrocatalytic oxidation performance of different alcohols. The Hg / HgO electrode was used as the reference electrode and the platinum mesh electrode was used as the counter electrode. The electrolyte was 1 M M KOH solution containing 1 M methanol, 1 M ethylene glycol or 1 M glycerol. The electrocatalytic oxidation performance of alcohols was tested in a three-electrode system on an electrochemical workstation.
[0044] In this invention, the drying in step (1) is carried out at room temperature, preferably 20~25℃; the drying time is preferably 3~8 hours, and more preferably 5~6 hours.
[0045] In this invention, the ratio of the palladium-antimony-platinum catalyst, ethanol, deionized water and naphthol is 1 mg: 500 μL: 500 μL: 15~20 μL, wherein the mass percentage concentration of naphthol is 10%.
[0046] The preferred mass concentration of Nafion is 5-20%, more preferably 10-15%.
[0047] This invention provides an application of electrocatalytic alcohol oxidation reaction at the anode of an alcohol fuel cell, including the electrocatalytic alcohol oxidation catalyst described in the above technical solution.
[0048] In some specific embodiments of the present invention, the alcohol substrate used in the electrocatalytic alcohol oxidation reaction is at least one of methanol, ethylene glycol, and glycerol; the concentration of alcohol in the alcohol solution is preferably 0.5~2 mol / L, more preferably 1~1.5 mol / L. The alcohol solution also contains an alkaline electrolyte, preferably KOH or NaOH, and its concentration in the alcohol solution is preferably 0.5~2 mol / L, more preferably 1~1.5 mol / L. The present invention also provides the application of the above-mentioned electrocatalytic alcohol oxidation catalyst in the electrocatalytic alcohol oxidation reaction, which is tested using a three-electrode system: a glassy carbon electrode coated with a carbon-supported palladium-antimony-platinum catalyst as the working electrode, an Hg / HgO electrode as the reference electrode, a platinum mesh as the counter electrode, and an alcohol solution as the electrolyte. The present invention provides a simple one-pot synthesis strategy, successfully realizing the controllable preparation of palladium-antimony-platinum ternary alloys. The obtained nanoparticles have uniform morphology and particle size, and the composition of the ternary alloy can be precisely controlled by adjusting the addition ratio of the metal precursor. By optimizing the electronic structure through component regulation, electrocatalytic performance can be maximized, thereby significantly enhancing the electrocatalytic oxidation activity of various alcohols (including methanol, ethylene glycol, and glycerol). This invention effectively overcomes the technical challenges of sluggish alcohol oxidation kinetics and insufficient stability in the anode reaction of direct alcohol fuel cells, providing a new technical approach for reducing fuel cell catalyst costs and promoting the development of clean energy electrocatalytic technology. The embodiments and comparative examples of this invention describe some implementations of the invention. However, this does not mean that the effects of the invention can only be achieved in these examples.
[0049] Example 1 (1) Place 10 mg of palladium acetylacetone, 10 mg of platinum acetylacetone, 10 mg of triphenylantimony, 5 mg of molybdenum hexacarbonyl, 60 mg of L-ascorbic acid, and 10 mL of oleylamine in a pressure-resistant bottle, seal, and sonicate for 15 minutes to fully dissolve and mix the precursors. Heat to 120 °C and maintain at this temperature for 120 minutes. After the reaction system cools to room temperature, transfer the reaction solution to a centrifuge tube and centrifuge at 6000 r / min for 5 minutes, discarding the supernatant. Add 1 mL of chloroform and 6 mL of ethanol to the bottom precipitate, sonicate to disperse, centrifuge again, discard the supernatant, and repeat the chloroform / ethanol washing operation 3 times. Then add 2 mL of acetone solution containing 100 mg of ammonium thiocyanate to the precipitate, sonicate for 15 minutes, centrifuge, discard the supernatant, and wash with acetone twice. Collect the bottom precipitate, dry it overnight at room temperature, and obtain Pd. 50 Sb 31 Pt 19 Ternary alloy nanomaterials.
[0050] Figure 1 The Pd prepared in this embodiment50 Sb 31 Pt 19 The characterization results of the nanomaterials are as follows: (a) Transmission electron microscopy (TEM) images show that the prepared material has good dispersion and a branched morphology; (b) XRD diffraction patterns show that the main diffraction peaks are shifted relative to the diffraction peaks of Pd, indicating that Sb / Pt has been successfully incorporated into the lattice and formed a ternary alloy phase; (c) High-angle annular dark-field scanning TEM images and (d) elemental distribution diagrams show that Pd, Sb, and Pt are uniformly distributed in the material; (e) Linear scanning energy dispersive X-ray spectroscopy (EDS) further confirms the uniform distribution of Pd, Sb, and Pt in the ternary alloy nanoparticles; (f) Energy dispersive X-ray spectroscopy (EDS) quantitative analysis results show that the atomic ratio of Pd, Sb, and Pt is approximately 50:31:19, indicating that a Pd-based nanomaterial was successfully prepared. 50 Sb 31 Pt 19 Ternary alloy nanomaterials.
[0051] (2) Pd 50 Sb 31 Pt 19 Ternary alloy nanomaterials are loaded with carbon black to obtain palladium-antimony-platinum catalyst 1.
[0052] Example 2
[0053] (1) Place 10 mg of palladium acetylacetone, 20 mg of platinum acetylacetone, 10 mg of triphenylantimony, 5 mg of molybdenum hexacarbonyl, 60 mg of L-ascorbic acid, and 10 mL of oleylamine into a pressure-resistant bottle, seal, and sonicate for 15 minutes to ensure complete dissolution and homogeneity of the precursors. Heat to 120 °C and maintain at this temperature for 120 minutes. After the reaction, centrifuge, wash, and dry as in Example 1 to obtain Pd. 40 Sb 31 Pt 29 Ternary alloy nanomaterials.
[0054] Figure 2 The Pd prepared in this embodiment 40 Sb 31 Pt 29 The characterization results of the nanomaterials are as follows: (a) Transmission electron microscopy (TEM) images show that the prepared material has good dispersion and a branched morphology; (b) XRD diffraction patterns show that the main diffraction peaks are shifted relative to the diffraction peaks of Pd, indicating that Sb / Pt has been successfully incorporated into the lattice and a ternary alloy phase has been formed; (c) Energy dispersive X-ray spectroscopy (EDS) quantitative analysis results show that the atomic ratio of Pd, Sb, and Pt is approximately 40:31:29, indicating that a Pd-based nanomaterial has been successfully prepared. 40 Sb 31 Pt 29 Ternary alloy nanomaterials.
[0055] (2) Pd 40 Sb 31 Pt 29 Ternary alloy nanomaterials are loaded with carbon black to obtain palladium-antimony-platinum catalyst 2.
[0056] Example 3
[0057] (1) Place 10 mg of palladium acetylacetone, 30 mg of platinum acetylacetone, 10 mg of triphenylantimony, 5 mg of molybdenum hexacarbonyl, 60 mg of L-ascorbic acid, and 10 mL of oleylamine into a pressure-resistant bottle, seal, and sonicate for 15 minutes to ensure complete dissolution and homogeneity of the precursors. Heat to 120 °C and maintain at this temperature for 120 minutes. After the reaction, centrifuge, wash, and dry as in Example 1 to obtain Pd. 27 Sb 23 Pt 50 Ternary alloy nanomaterials.
[0058] Figure 3 The Pd prepared in this embodiment 27 Sb 23 Pt 50 The characterization results of the nanomaterials are as follows: (a) Transmission electron microscopy (TEM) images show that the prepared material has good dispersion and a branched morphology; (b) XRD diffraction patterns show that the main diffraction peaks are shifted relative to the diffraction peaks of Pd, indicating that Sb / Pt has been successfully incorporated into the lattice and formed a ternary alloy phase; (c) High-angle annular dark-field scanning TEM images and (d) elemental distribution diagrams show that Pd, Sb, and Pt are uniformly distributed in the material; (e) Linear scanning energy dispersive X-ray spectroscopy (EDS) further confirms the uniform distribution of Pd, Sb, and Pt in the ternary alloy nanoparticles; (f) Energy dispersive X-ray spectroscopy (EDS) quantitative analysis results show that the atomic ratio of Pd, Sb, and Pt is approximately 27:23:50, indicating that a Pd-based nanomaterial was successfully prepared. 27 Sb 23 Pt 50 Ternary alloy nanomaterials.
[0059] (2) Pd 27 Sb 23 Pt 50 Ternary alloy nanomaterials are loaded with carbon black to obtain palladium-antimony-platinum catalyst 3.
[0060] Example 4
[0061] (1) Place 10 mg of palladium acetylacetone, 40 mg of platinum acetylacetone, 10 mg of triphenylantimony, 5 mg of molybdenum hexacarbonyl, 60 mg of L-ascorbic acid, and 10 mL of oleylamine into a pressure-resistant bottle, seal, and sonicate for 15 minutes to ensure complete dissolution and homogeneity of the precursors. Heat to 120 °C and maintain at this temperature for 120 minutes. After the reaction, centrifuge, wash, and dry as in Example 1 to obtain Pd. 25 Sb 21 Pt 54 Ternary alloy nanomaterials.
[0062] Figure 4 The Pd prepared in this embodiment 25 Sb 21 Pt 54 The characterization results of the nanomaterials are as follows: (a) Transmission electron microscopy (TEM) images show that the prepared material has good dispersion and a branched morphology; (b) XRD diffraction patterns show that the main diffraction peaks are shifted relative to the diffraction peaks of Pd, indicating that Sb / Pt has been successfully incorporated into the lattice and a ternary alloy phase has been formed; (c) Energy dispersive X-ray spectroscopy (EDS) quantitative analysis results show that the atomic ratio of Pd, Sb, and Pt is approximately 25:21:54, indicating that a Pd-based nanomaterial has been successfully prepared. 25 Sb 21 Pt 54 Ternary alloy nanomaterials.
[0063] (2) Pd 25 Sb 21 Pt 54 Ternary alloy nanomaterials are loaded with carbon black to obtain palladium-antimony-platinum catalyst 4.
[0064] Example 5
[0065] (1) Place 10 mg of palladium acetylacetone, 50 mg of platinum acetylacetone, 10 mg of triphenylantimony, 5 mg of molybdenum hexacarbonyl, 60 mg of L-ascorbic acid, and 10 mL of oleylamine into a pressure-resistant bottle, seal, and sonicate for 15 minutes to ensure complete dissolution and homogeneity of the precursors. Heat to 120 °C and maintain at this temperature for 120 minutes. After the reaction, centrifuge, wash, and dry as in Example 1 to obtain Pd. 23 Sb 19 Pt 58 Ternary alloy nanomaterials.
[0066] Figure 5 The Pd prepared in this embodiment 23 Sb 19 Pt 58The characterization results of the nanomaterials are as follows: (a) Transmission electron microscopy (TEM) images show that the prepared material has good dispersion and a branched morphology; (b) XRD diffraction patterns show that the main diffraction peaks are shifted relative to the diffraction peaks of Pd, indicating that Sb / Pt has been successfully incorporated into the lattice and formed a ternary alloy phase; (c) High-angle annular dark-field scanning TEM images and (d) elemental distribution diagrams show that Pd, Sb, and Pt are uniformly distributed in the material; (e) Linear scanning energy dispersive X-ray spectroscopy (EDS) further confirms the uniform distribution of Pd, Sb, and Pt in the ternary alloy nanoparticles; (f) Energy dispersive X-ray spectroscopy (EDS) quantitative analysis results show that the atomic ratio of Pd, Sb, and Pt is approximately 23:19:58, indicating that a Pd-based nanomaterial was successfully prepared. 23 Sb 19 Pt 58 Ternary alloy nanomaterials.
[0067] (2) Pd 23 Sb 19 Pt 58 Ternary alloy nanomaterials are loaded with carbon black to obtain palladium-antimony-platinum catalyst 5.
[0068] Comparative Example 1 (1) Place 10 mg of palladium acetylacetonate, 10 mg of triphenylantimony, 5 mg of molybdenum hexacarbonyl, 60 mg of L-ascorbic acid, and 10 mL of oleylamine in a pressure-resistant bottle, seal, and sonicate for 15 minutes to ensure complete dissolution and homogeneity of the precursors. Heat to 120 °C and maintain at this temperature for 120 minutes. After the reaction, centrifuge, wash, and dry as in Example 1 to obtain Pd. 69 Sb 31 Binary alloy nanomaterials.
[0069] Figure 6 The Pd prepared in this embodiment 69 Sb 31 The characterization results of the nanomaterials are as follows: (a) Transmission electron microscopy (TEM) images show that the prepared material has good dispersion and a branched morphology; (b) XRD diffraction patterns show that the main diffraction peaks are shifted relative to the diffraction peaks of Pd, indicating that Sb has been successfully incorporated into the lattice and formed a binary alloy phase; (c) Energy dispersive X-ray spectroscopy (EDS) quantitative analysis results show that the atomic ratio of Pd to Sb is approximately 69:31, indicating that a Pd-based nanomaterial was successfully prepared. 69 Sb 31 Binary alloy nanomaterials.
[0070] (2) Pd 69 Sb 31 A palladium-antimony catalyst is obtained by loading binary alloy nanomaterials with carbon black.
[0071] Comparative Example 2 A commercial Pd / C catalyst (Pd loading 10 wt%) was used as a control sample and was ultrasonically dispersed before use.
[0072] Application Example 1 The carbon-supported palladium-antimony-platinum catalysts prepared in Examples 1-5 and the carbon-supported Pd catalysts prepared in Comparative Example 1 were respectively compared. 69 Sb 31 The catalyst and comparative example 2: A commercial Pd / C catalyst was supported on a glassy carbon electrode as the working electrode, with an Hg / HgO electrode as the reference electrode and a platinum mesh as the counter electrode. A 1 M KOH + 1 M methanol solution was used as the electrolyte. Cyclic voltammetry and chronoamperometry were performed on an electrochemical workstation. The scan rate for cyclic voltammetry was 50 mV / s, and the test potential for chronoamperometry was -0.124 V, with a test time of 10 hours.
[0073] Figure 7 Figure a shows a comparison of cyclic voltammetry curves for different catalysts used in the methanol oxidation reaction in this application example. The results indicate that the mass activity of the carbon-supported ternary palladium-antimony-platinum catalysts in Examples 1-5 is significantly higher than that of the carbon-supported binary Pd catalyst in Comparative Example 1. 69 Sb 31 Mass activity of the catalyst and comparative example 2 commercial Pd / C catalyst, wherein: carbon-supported Pd in Example 1 50 Sb 31 Pt 19 The catalyst's mass activity is 2.07 A / mg. Pd+Pt Carbon-supported Pd in Example 2 40 Sb 31 Pt 29 The catalyst's mass activity is 3.14 A / mg. Pd+Pt Carbon-supported Pd in Example 3 27 Sb 23 Pt 50 The catalyst's mass activity is 4.21 A / mg. Pd+Pt Carbon-supported Pd in Example 4 25 Sb 21 Pt 54 The catalyst's mass activity is 3.01 A / mg. Pd+Pt Carbon-supported Pd in Example 5 23 Sb 19 Pt 58 The catalyst's mass activity is 3.04 A / mg. Pd+Pt Comparative Example 1: Carbon-supported Pd 69 Sb 31 The catalyst's mass activity is 1.09 A / mg. Pd+Pt And the comparative example 2 showed that the commercial Pd / C catalyst had a mass activity of 0.44 A / mg.Pd Of all the catalysts, Example 3 showed the best performance with carbon-supported Pd. 27 Sb 23 Pt 50 The catalyst exhibits optimal mass activity. Therefore, the catalyst based on palladium-antimony-platinum ternary alloy nanomaterials described in this invention can effectively improve the mass activity of the electrocatalytic methanol oxidation reaction.
[0074] Figure 7 In Figure b, the specific activity is calculated after normalizing the current to the corresponding electrochemical active area. The results show that the specific activity of the carbon-supported ternary palladium-antimony-platinum catalysts in Examples 1-5 is significantly higher than that of the carbon-supported binary Pd catalyst in Comparative Example 1. 69 Sb 31 The specific activity of the catalyst and the commercial Pd / C catalyst of Comparative Example 2, wherein: the carbon-supported Pd catalyst of Example 1 50 Sb 31 Pt 19 The catalyst specific activity is 15.36 mA / cm². 2 Carbon-supported Pd in Example 2 40 Sb 31 Pt 29 The catalyst specific activity is 23.26 mA / cm². 2 Carbon-supported Pd in Example 3 27 Sb 23 Pt 50 The catalyst specific activity is 30.39 mA / cm². 2 Carbon-supported Pd in Example 4 25 Sb 21 Pt 54 The catalyst specific activity is 21.89 mA / cm². 2 Carbon-supported Pd in Example 5 23 Sb 19 Pt 58 The catalyst specific activity is 22.27 mA / cm². 2 Comparative Example 1: Carbon-supported Pd 69 Sb 31 The catalyst specific activity is 8.25 mA / cm². 2 And the specific activity of the commercial Pd / C catalyst in Comparative Example 2 was 1.09 mA / cm². 2 Of all the catalysts, Example 3 showed the best performance with carbon-supported Pd. 27 Sb 23 Pt 50 The catalyst exhibits optimal specific activity. Therefore, the catalyst based on palladium-antimony-platinum ternary alloy nanomaterials described in this invention can effectively enhance the specific activity of the electrocatalytic methanol oxidation reaction.
[0075] Figure 7In the figure, c represents the calculated Tafel slope for different catalysts. The results show that the Tafel slopes of the carbon-supported ternary palladium-antimony-platinum catalysts in Examples 1-5 are significantly lower than those of the carbon-supported binary Pd catalyst in Comparative Example 1. 69 Sb 31 Tafel slopes of the catalyst and the commercial Pd / C catalyst of Comparative Example 2, wherein: the carbon-supported Pd of Example 1 50 Sb 31 Pt 19 The catalyst Tafel slope is 126.4 mVdec. -1 Carbon-supported Pd in Example 2 40 Sb 31 Pt 29 The catalyst Tafel slope is 99.5 mV dec. -1 Carbon-supported Pd in Example 3 27 Sb 23 Pt 50 The catalyst Tafel slope is 95.3 mV dec. -1 Carbon-supported Pd in Example 4 25 Sb 21 Pt 54 The catalyst Tafel slope is 124.3 mV dec. -1 Carbon-supported Pd in Example 5 23 Sb 19 Pt 58 The catalyst Tafel slope is 105.8 mVdec. -1 Comparative Example 1: Carbon-supported Pd 69 Sb 31 The catalyst Tafel slope is 149.5 mV dec. -1 And in Comparative Example 2, the Tafel slope of the commercial Pd / C catalyst was 325.7 mV dec. -1 Of all the catalysts, Example 3 showed the best performance with carbon-supported Pd. 27 Sb 23 Pt 50 The catalyst exhibits a minimal Tafel slope. A smaller Tafel slope is an important indicator of catalyst reaction kinetics, and the catalyst based on palladium-antimony-platinum ternary alloy nanomaterials described in this invention can effectively enhance the kinetics of the electrocatalytic methanol oxidation reaction.
[0076] Figure 7 Figure d shows a comparison of chronoamperometry test curves for different catalysts used in the methanol oxidation reaction. During the 10-hour test period, the carbon-supported palladium-antimony-platinum catalysts prepared in Examples 1-5 showed a significant difference compared to the carbon-supported Pd catalyst in Comparative Example 1. 69 Sb 31Both the commercial Pd / C catalyst in Comparative Example 2 and the catalyst in Comparative Example 3 exhibited higher mass activity retention, indicating that the palladium-antimony-platinum ternary alloy nanomaterial catalyst described in this invention can effectively improve the long-term stability of electrocatalytic methanol oxidation. Specifically, the carbon-supported Pd catalyst in Example 3... 27 Sb 23 Pt 50 The catalyst exhibits the best mass activity retention capability, indicating that the catalyst based on the ternary palladium-antimony-platinum nanoalloy can significantly improve the stability of the electrocatalytic methanol oxidation reaction. Among all catalysts, the carbon-supported Pd catalyst in Example 3 is the best. 27 Sb 23 Pt 50 The catalyst exhibits optimal electrocatalytic methanol oxidation stability.
[0077] Application Example 2 The carbon-supported palladium-antimony-platinum catalysts prepared in Examples 1-5 and the carbon-supported Pd catalysts prepared in Comparative Example 1 were respectively compared. 69 Sb 31 Catalyst and Comparative Example 2: A commercial Pd / C catalyst was supported on a glassy carbon electrode as the working electrode, with an Hg / HgO electrode as the reference electrode and a platinum mesh as the counter electrode. A 1 M KOH + 1 M ethylene glycol solution was used as the electrolyte. Cyclic voltammetry and chronoamperometry were performed on an electrochemical workstation. The scan rate for cyclic voltammetry was 50 mV / s, and the test potential for chronopotentialography was -0.124 V, with a test time of 2 hours.
[0078] Figure 8 Figure a shows a comparison of cyclic voltammetry curves for different catalysts used in the ethylene glycol oxidation reaction in this application example. The results indicate that the mass activity of the carbon-supported ternary palladium-antimony-platinum catalysts in Examples 1-5 is significantly higher than that of the carbon-supported binary Pd catalyst in Comparative Example 1. 69 Sb 31 Mass activity of the catalyst and comparative example 2 commercial Pd / C catalyst, wherein: carbon-supported Pd in Example 1 50 Sb 31 Pt 19 The catalyst's mass activity is 3.30 A / mg. Pd+Pt Carbon-supported Pd in Example 2 40 Sb 31 Pt 29 The catalyst's mass activity is 6.07 A / mg. Pd+Pt Carbon-supported Pd in Example 3 27 Sb 23 Pt 50 The catalyst's mass activity is 7.59 A / mg. Pd+Pt Carbon-supported Pd in Example 4 25 Sb 21 Pt 54The catalyst's mass activity is 6.10 A / mg. Pd+Pt Carbon-supported Pd in Example 5 23 Sb 19 Pt 58 The catalyst's mass activity is 7.30 A / mg. Pd+Pt Comparative Example 1: Carbon-supported Pd 69 Sb 31 The catalyst's mass activity is 2.57 A / mg. Pd+Pt And the comparative example 2 showed that the commercial Pd / C catalyst had a mass activity of 2.03 A / mg. Pd Of all the catalysts, Example 3 showed the best performance with carbon-supported Pd. 27 Sb 23 Pt 50 The catalyst exhibits optimal mass activity. Therefore, the catalyst based on palladium-antimony-platinum ternary alloy nanomaterials described in this invention can effectively improve the mass activity of the electrocatalytic ethylene glycol oxidation reaction.
[0079] Figure 8 In Figure b, the specific activity is calculated after normalizing the current to the corresponding electrochemical active area. The results show that the specific activity of the carbon-supported ternary palladium-antimony-platinum catalysts in Examples 1-5 is significantly higher than that of the carbon-supported binary Pd catalyst in Comparative Example 1. 69 Sb 31 The specific activity of the catalyst and the commercial Pd / C catalyst of Comparative Example 2, wherein: the carbon-supported Pd catalyst of Example 1 50 Sb 31 Pt 19 The catalyst specific activity is 24.64 mA / cm². 2 Carbon-supported Pd in Example 2 40 Sb 31 Pt 29 The catalyst specific activity is 44.78 mA / cm². 2 Carbon-supported Pd in Example 3 27 Sb 23 Pt 50 The catalyst specific activity is 54.57 mA / cm². 2 Carbon-supported Pd in Example 4 25 Sb 21 Pt 54 The catalyst specific activity is 44.68 mA / cm². 2 Carbon-supported Pd in Example 5 23 Sb 19 Pt 58 The catalyst specific activity is 53.16 mA / cm². 2 Comparative Example 1: Carbon-supported Pd 69 Sb 31 The catalyst specific activity is 18.98 mA / cm². 2And the specific activity of the commercial Pd / C catalyst in Comparative Example 2 was 5.17 mA / cm². 2 Of all the catalysts, Example 3 showed the best performance with carbon-supported Pd. 27 Sb 23 Pt 50 The catalyst exhibits optimal specific activity. Therefore, the catalyst based on palladium-antimony-platinum ternary alloy nanomaterials described in this invention can effectively enhance the specific activity of the electrocatalytic ethylene glycol oxidation reaction.
[0080] Figure 8 In the figure, c represents the calculated Tafel slope for different catalysts. The results show that the Tafel slopes of the carbon-supported ternary palladium-antimony-platinum catalysts in Examples 1-5 are significantly lower than those of the carbon-supported binary Pd catalyst in Comparative Example 1. 69 Sb 31 Tafel slopes of the catalyst and the commercial Pd / C catalyst of Comparative Example 2, wherein: the carbon-supported Pd of Example 1 50 Sb 31 Pt 19 The catalyst Tafel slope is 141.4 mVdec. -1 Carbon-supported Pd in Example 2 40 Sb 31 Pt 29 The catalyst Tafel slope is 137.5 mV dec. -1 Carbon-supported Pd in Example 3 27 Sb 23 Pt 50 The catalyst Tafel slope is 63.0 mV dec. -1 Carbon-supported Pd in Example 4 25 Sb 21 Pt 54 The catalyst Tafel slope is 144.2 mV dec. -1 Carbon-supported Pd in Example 5 23 Sb 19 Pt 58 The catalyst Tafel slope is 95.8 mVdec. -1 Comparative Example 1: Carbon-supported Pd 69 Sb 31 The catalyst Tafel slope is 144.2 mV dec. -1 And the Tafel slope of the commercial Pd / C catalyst in Comparative Example 2 was 186.9 mV dec. -1 Of all the catalysts, Example 3 showed the best performance with carbon-supported Pd. 27 Sb 23 Pt 50The catalyst exhibits a minimal Tafel slope. A smaller Tafel slope is an important indicator of catalytic reaction kinetics. The catalyst based on palladium-antimony-platinum ternary alloy nanomaterials described in this invention can effectively enhance the kinetics of the electrocatalytic oxidation of ethylene glycol.
[0081] Figure 8 Figure d shows a comparison of chronoamperometry test curves for different catalysts used in the ethylene glycol oxidation reaction. During the 2-hour test period, the carbon-supported palladium-antimony-platinum catalysts prepared in Examples 1-5 were compared to the carbon-supported Pd catalyst in Comparative Example 1. 69 Sb 31 Both the commercial Pd / C catalyst in Comparative Example 2 and the catalyst in Comparative Example 3 exhibited higher mass activity retention, indicating that the palladium-antimony-platinum ternary alloy nanomaterial catalyst described in this invention can effectively improve the long-term stability of electrocatalytic ethylene glycol oxidation. Specifically, the carbon-supported Pd catalyst in Example 3... 27 Sb 23 Pt 50 The catalyst exhibits the best mass activity retention capability, indicating that the catalyst based on the ternary palladium-antimony-platinum nanoalloy can significantly improve the stability of the electrocatalytic ethylene glycol oxidation reaction. Among all catalysts, the carbon-supported Pd catalyst in Example 3 is the best. 27 Sb 23 Pt 50 The catalyst exhibits optimal electrocatalytic stability for ethylene glycol oxidation.
[0082] Application Example 3 The carbon-supported palladium-antimony-platinum catalysts prepared in Examples 1-5 and the carbon-supported Pd catalysts prepared in Comparative Example 1 were respectively compared. 69 Sb 31 Catalyst and Comparative Example 2: A commercial Pd / C catalyst was supported on a glassy carbon electrode as the working electrode, with an Hg / HgO electrode as the reference electrode and a platinum mesh as the counter electrode. A 1 M KOH + 1 M glycerol solution was used as the electrolyte. Cyclic voltammetry and chronoamperometry were performed on an electrochemical workstation. The scan rate for cyclic voltammetry was 50 mV / s, and the test potential for chronoamperometry was -0.124 V, with a test time of 2 hours.
[0083] Figure 9 Figure a shows a comparison of cyclic voltammetry curves for different catalysts used in the glycerol oxidation reaction in this application example. The results indicate that the mass activity of the carbon-supported ternary palladium-antimony-platinum catalysts in Examples 1-5 is significantly higher than that of the carbon-supported binary Pd catalyst in Comparative Example 1. 69 Sb 31 Mass activity of the catalyst and comparative example 2 commercial Pd / C catalyst, wherein: carbon-supported Pd in Example 1 50 Sb 31 Pt 19 The catalyst's mass activity is 2.58 A / mg. Pd+PtCarbon-supported Pd in Example 2 40 Sb 31 Pt 29 The catalyst's mass activity is 2.98 A / mg. Pd+Pt Carbon-supported Pd in Example 3 27 Sb 23 Pt 50 The catalyst's mass activity is 3.95 A / mg. Pd+Pt Carbon-supported Pd in Example 4 25 Sb 21 Pt 54 The catalyst's mass activity is 2.54 A / mg. Pd+Pt Carbon-supported Pd in Example 5 23 Sb 19 Pt 58 The catalyst's mass activity is 2.68 A / mg. Pd+Pt Comparative Example 1: Carbon-supported Pd 69 Sb 31 The catalyst's mass activity is 1.46 A / mg. Pd+Pt And the comparative example 2 showed that the commercial Pd / C catalyst had a mass activity of 0.93 A / mg. Pd Of all the catalysts, Example 3 showed the best performance with carbon-supported Pd. 27 Sb 23 Pt 50 The catalyst exhibits optimal mass activity. Therefore, the catalyst based on palladium-antimony-platinum ternary alloy nanomaterials described in this invention can effectively improve the mass activity of the electrocatalytic oxidation of glycerol.
[0084] Figure 9 In Figure b, the specific activity is calculated after normalizing the current to the corresponding electrochemical active area. The results show that the specific activity of the carbon-supported ternary palladium-antimony-platinum catalysts in Examples 1-5 is significantly higher than that of the carbon-supported binary Pd catalyst in Comparative Example 1. 69 Sb 31 The specific activity of the catalyst and the commercial Pd / C catalyst of Comparative Example 2, wherein: the carbon-supported Pd catalyst of Example 1 50 Sb 31 Pt 19 The catalyst specific activity is 19.20 mA / cm². 2 Carbon-supported Pd in Example 2 40 Sb 31 Pt 29 The catalyst specific activity is 22.07 mA / cm². 2 Carbon-supported Pd in Example 3 27 Sb 23 Pt 50 The catalyst specific activity is 28.52 mA / cm². 2 Carbon-supported Pd in Example 425 Sb 21 Pt 54 The catalyst specific activity is 18.68 mA / cm². 2 Carbon-supported Pd in Example 5 23 Sb 19 Pt 58 The catalyst specific activity is 19.57 mA / cm². 2 Comparative Example 1: Carbon-supported Pd 69 Sb 31 The catalyst specific activity is 11.06 mA / cm². 2 And the specific activity of the commercial Pd / C catalyst in Comparative Example 2 is 2.40 mA / cm². 2 Of all the catalysts, Example 3 showed the best performance with carbon-supported Pd. 27 Sb 23 Pt 50 The catalyst exhibits optimal specific activity. Therefore, the catalyst based on palladium-antimony-platinum ternary alloy nanomaterials described in this invention can effectively enhance the specific activity of the electrocatalytic oxidation of glycerol.
[0085] Figure 9 In the figure, c represents the calculated Tafel slope for different catalysts. The results show that the Tafel slopes of the carbon-supported ternary palladium-antimony-platinum catalysts in Examples 1-5 are significantly lower than those of the carbon-supported binary Pd catalyst in Comparative Example 1. 69 Sb 31 Tafel slopes of the catalyst and the commercial Pd / C catalyst of Comparative Example 2, wherein: the carbon-supported Pd of Example 1 50 Sb 31 Pt 19 The catalyst Tafel slope is 154.7 mVdec. -1 Carbon-supported Pd in Example 2 40 Sb 31 Pt 29 The catalyst Tafel slope is 151.9 mV dec. -1 Carbon-supported Pd in Example 3 27 Sb 23 Pt 50 The catalyst Tafel slope is 151.1 mV dec. -1 Carbon-supported Pd in Example 4 25 Sb 21 Pt 54 The catalyst Tafel slope is 158.0 mV dec. -1 Carbon-supported Pd in Example 5 23 Sb 19 Pt 58 The catalyst Tafel slope is 153.0 mVdec. -1 Comparative Example 1: Carbon-supported Pd69 Sb 31 The catalyst Tafel slope is 163.9 mV dec. -1 And in Comparative Example 2, the Tafel slope of the commercial Pd / C catalyst was 168.8 mV dec. -1 Of all the catalysts, Example 3 showed the best performance with carbon-supported Pd. 27 Sb 23 Pt 50 The catalyst exhibits a minimal Tafel slope. A smaller Tafel slope is an important indicator of catalyst reaction kinetics, and the catalyst based on a palladium-antimony-platinum ternary alloy nanomaterial described in this invention can effectively enhance the kinetics of the electrocatalytic oxidation of glycerol.
[0086] Figure 9 Figure d shows a comparison of chronoamperometry test curves for different catalysts used in the oxidation of glycerol. During the 2-hour test period, the carbon-supported palladium-antimony-platinum catalysts prepared in Examples 1-5 were compared with the carbon-supported Pd catalyst in Comparative Example 1. 69 Sb 31 Both the commercial Pd / C catalyst in Comparative Example 2 and the catalyst in Comparative Example 3 exhibited higher mass activity retention, indicating that the palladium-antimony-platinum ternary alloy nanomaterial catalyst described in this invention can effectively improve the long-term stability of electrocatalytic glycerol oxidation. Specifically, the carbon-supported Pd catalyst in Example 3... 27 Sb 23 Pt 50 The catalyst exhibits the best mass activity retention capability, indicating that the catalyst based on the ternary palladium-antimony-platinum nanoalloy can significantly improve the stability of the electrocatalytic oxidation of glycerol. Among all catalysts, the carbon-supported Pd catalyst in Example 3 is the best. 27 Sb 23 Pt 50 The catalyst exhibits optimal electrocatalytic stability for glycerol oxidation.
[0087] The test results of Application Examples 1-3 above show that the Pd-Sb-Pt ternary alloy catalyst prepared by this invention exhibits excellent electrocatalytic oxidation activity for alcohol substrates (including methanol, ethylene glycol, and glycerol) with different carbon chain lengths and molecular structures, indicating that this ternary alloy system has good universal application value in the field of direct alcohol fuel cell anode catalysis. The above description is only a preferred embodiment of this invention. It should be noted that those skilled in the art can make several improvements and modifications without departing from the principle of this invention, and these improvements and modifications should also be considered within the scope of protection of this invention.
Claims
1. A method for controlling the composition of a palladium-antimony-platinum catalyst, characterized in that, Includes the following steps: A certain amount of palladium metal precursor, platinum metal precursor, platinum metal precursor, structure directing agent, reducing agent and solvent are sealed and mixed evenly, and then heated to react for a period of time. After the reaction is completed, the mixture is cooled to room temperature to obtain a nanomaterial solution. After the reaction is completed, the palladium-antimony-platinum nanomaterial is washed, dried and then loaded with carbon black to obtain a palladium-antimony-platinum catalyst.
2. The component regulation method according to claim 1, characterized in that, The palladium metal precursor is palladium acetylacetonate; the platinum metal precursor is platinum acetylacetonate; the platinum metal precursor is triphenylantimony; the structure directing agent is molybdenum hexacarbonyl; the reducing agent is L-ascorbic acid; and the solvent is oleylamine. The ratio of acetylacetone palladium, triphenylantimony, acetylacetone platinum, hexacarbonyl molybdenum, L-ascorbic acid to oleylamine is 1 mg : 1 mg : 1~5 mg : 0.5 mg : 6 mg : 1 mL.
3. The component regulation method according to claim 2, characterized in that, The composition of the palladium-antimony-platinum catalyst can be controlled by changing the amount of platinum acetylacetone added. The composition ratio of the palladium-antimony-platinum catalyst includes, but is not limited to, Pd. 50 Sb 31 Pt 19 Pd 40 Sb 31 Pt 29 Pd 27 Sb 23 Pt 50 Pd 25 Sb 21 Pt 54 or Pd 23 Sb 19 Pt 58 .
4. The component regulation method according to claim 1, characterized in that, The heating reaction temperature is 100~140℃; the reaction time is 80~150 minutes.
5. The component regulation method according to claim 1, characterized in that, The washing process is carried out in two steps. First, the washing is performed with a chloroform / ethanol solution, wherein the volume ratio of chloroform to ethanol is 1:(5~7); then, the washing is performed with an ammonium thiocyanate / acetone solution, wherein the volume ratio of ammonium thiocyanate to acetone is (30~70) mg:1 mL.
6. The component regulation method according to claim 1, characterized in that, The steps for loading palladium-antimony-platinum nanomaterials with carbon black are as follows: the mass ratio of dried palladium-antimony-platinum nanomaterials to carbon black is 1:3, and the carbon black is Super P type carbon black.
7. The application of the palladium-antimony-platinum catalyst prepared by the component regulation method according to any one of claims 1 to 6 in the electrocatalytic alcohol oxidation catalyst.
8. The application as described in claim 7, characterized in that, Includes the following steps: (1) The palladium-antimony-platinum catalyst was dispersed in ethanol, and then deionized water and naphthol were added. The mixture was then ultrasonically mixed to obtain a palladium-antimony-platinum catalyst dispersion. (2) The palladium-antimony-platinum catalyst dispersion from step (1) is uniformly coated onto the surface of a glassy carbon electrode and dried to obtain the palladium-antimony-platinum working electrode. (3) Test the electrocatalytic oxidation performance of different alcohols in a three-electrode system using the working electrode from step (2), wherein the alcohols include, but are not limited to, methanol, ethylene glycol or glycerol.
9. The application according to claim 8, characterized in that, In step (1), the ratio of the palladium-antimony-platinum catalyst, ethanol, deionized water and naphthol is 1 mg: 500 μL: 500 μL: 15~20 μL, wherein the mass percentage concentration of naphthol is 10%.
10. The application as described in claim 7, characterized in that, The alcohol is methanol, ethylene glycol, or glycerol.